Early mobilization in enhanced recovery after surgery pathways: current evidence and recent advancements - Tazreean, Reeana; Nelson, Gregg; Twomey, Rosie (Journal of Comparative Effectiveness Research, 2022)
Early mobilization is a crucial component of enhanced recovery after surgery (ERAS) pathways that counteract the adverse physiological consequences of surgical stress and immobilization. Early mobilization reduces the risk of postoperative complications, accelerates the recovery of functional walking capacity, positively impacts several patient-reported outcomes and reduces hospital length of stay, thereby reducing care costs. Modifiable barriers to early mobilization include a lack of education and a lack of resources. Education and clinical decision-making tools can improve compliance with ERAS mobilization recommendations and create a culture that prioritizes perioperative physical activity. Recent advances include real-time feedback of mobilization quantity using wearable technology and combining ERAS with exercise prehabilitation. ERAS guidelines should emphasize the benefits of structured postoperative mobilization.